Place & Mainstream-Israel Contemporary Sculpture. (Seoul : The National Museum of Contemporary Art, 1992)
Averbuch, Ilan ; Ben-David, Zadok ; Berman-Kadim, Reuven ; Buch, Bilu ; Brokovsky, Joshua ; Cohen Gan, Pinchas ; Dagan, Elisha ; Dominey, Drora ; Dorchin, Yaakov ; Efrat, Benni ; Eshet, Pinchas ; Fainaru, Belu Simion ; Gechtman, Gideon ; Gejer, Teresa ; Gershuni, Bianka Eshel ; Gitlin, Michael ; Golombek, Itshak ; Gross, Michael ; Kadishman, Menashe ; Geller, Dina Kahma ; Kantor, Zvika ; Karavan, Dany ; Klasmer, Gabi ; etc.
Place & Mainstream-Israel Contemporary Sculpture, The National Museum of Contemporary Art, Seoul, 25.03. - 24.04.1992
boek
Keywords: Israel